Influence of Welfare Against Teacher Performance - Nur Jamilah; Renny Oktafia; Siti Ruchana (International Consortium of Education and Culture Research Studies, 2020)
This study has a background problem where teacher performance is declining, this is characterized by Distrust and teacher disloyality, many empty hours and teacher enthusiasm in teaching is decreasing. School leaders try to provide teacher welfare in the hope that teacher performance will increase. This study aims to determine whether there is an influence between teacher welfare with teacher performance. This research uses a quantitative approach using a questionnaire as the primary data. The population in this study were 55 teachers in SMA Muhamadiyah 2 Sidoarjo. The data analysis technique uses multiple linear regression test, the hypothesis test uses the t test which was previously tested with the validity and reliability test and is evaluated with the assumption test. The results of this study produce that welfare affects the performance of teachers so that the better the welfare of teachers in schools, the enthusiasm of teachers in teaching and activities at school increases. Of course this also needs to be done monitoring of teaching teachers so that the welfare provided by schools can take place effectively.